PERKEMBANGAN TERKINI MANIFESTASI KLINIS FRAMBUSIA - Natasha, Joanne; Menaldi, Sri Linuwih SW; Irawan, Yudo; Novianto, Endi (Media Dermato-Venereologica Indonesiana, 2024)
Yaws, a neglected tropical disease, is still become the health problem in several countries. World Health Organization has proposed 2030 goals for yaws eradication after the previous target has not been achieved. Indonesia is still one of the largest contributors to yaws cases in Southeast Asia. The variety of lesions and the development of atypical clinical features make the yaws diagnose as a challenge. WHO guideline is used as a reference to determine the clinical manifestations, divided into early stage (infectious) lesions to advanced (non-infectious) yaws lesions. Yaws clinical features should be mastered by health workers in Indonesia, considering that the establishment of suspected cases begin with a clinical examination then confirmed by serological test. Several recent clinical surveillance had not reported early-stage lesions as the most common clinical finding, but rather had scars which was previously removed from the modified WHO guidelines. Missed diagnosis causes continually transmission.